1972
DOI: 10.1128/aem.24.6.891-898.1972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Oxygen Tension on Staphylococcal Growth and Enterotoxin Formation in Fermented Sausage

Abstract: Commercial fermented sausages that contained significant numbers of viable coagulase-positive staphylococci were found to have the growth localized in the outermost areas of the sausage where oxygen tension was highest. Staphylococci were found to be more acid-tolerant aerobically than anaerobically. With

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 9 publications
4
25
0
Order By: Relevance
“…The results of this experiment indicated that pediococci were more efficient controlling the anaerobic growth of some strains of S. aureus in fermented/cured meat environments. Similar observations were recorded by Barber and Deibel(1972). On the other hand, one may find reports showing that LAB were able to control the aerobic growth of S. aureus (Raccach, 1981a) and the formation of enterotoxin (Niskanen and Nurmi, 1976).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The results of this experiment indicated that pediococci were more efficient controlling the anaerobic growth of some strains of S. aureus in fermented/cured meat environments. Similar observations were recorded by Barber and Deibel(1972). On the other hand, one may find reports showing that LAB were able to control the aerobic growth of S. aureus (Raccach, 1981a) and the formation of enterotoxin (Niskanen and Nurmi, 1976).…”
Section: Resultssupporting
confidence: 79%
“…The largest increase of S. aureus was noted in the nitrite-free product. Nitrite controlled significantly (P < 0.01) the aerobic and anaerobic growth of the pathogen keeping it below the level associated with enterotoxin production (Barber and Deibel, 1972). Other reports found nitrite either ineffective (Hallerbach and Potter, 1981) or only effective against the anaerobic growth of S. aureus (Labots, 1976).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In Pepperoni (35°C) containing BHA and BHT the population of S. aureus attained a level of 1.7 x lo7 cellig after 18 hr. This level is associated with enterotoxin production (Barber and Deibel 1972). The preservative system containing the phenolic antioxidants and P pentosaceus controlled the growth of the pathogen by 1 and 2 log,,, cycles after 10 and 18 hr, respectively.…”
Section: Factors Modifying Antimicrobial Activity Of Phenolic Antioximentioning
confidence: 99%
“…Nitrite became more effective as an inhibitor when pH decreased from 7.0 t o 5.0 (Castellani and Niven 1955). In fermented sausages containing nitrite, the inner core (anaerobic portion) contained fewer staphylococci than the surface (aerobic portion) (Barber and Deibel 1972;Labots 1976;Lee et al 1977). Anaerobic inhibition of staphylococcal growth by nitrite is so well established that the National Research Council's Committee on Food Protection criterion for evaluation of enterotoxin formation in fermented sausages consists of the enumeration of coagulase positive S. aureus only in the outer 6 to 7 mm portion (National Research Council 1975).…”
Section: Introductionmentioning
confidence: 99%